ANALYSIS OF TRANSPORTATION OBJECTS IN SEWING INDUSTRY - BILASHOV, KOSTIANTYN; KOVALIOV, YURII; BILOTSKA, LARYSA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The article presents a detailed classification and analysis of the main transported objects in modern garment manufacturing, with particular attention to their physical and mechanical properties, packaging types, and impact on the organization of logistics processes. The study identifies five major groups of transported objects: roll materials (fabrics, linings, adhesives), cut garment components, sets of parts for assembly operations, semi-finished products during finishing stages, and ready-made garments. Each group is examined in terms of typical examples, transportation containers, and associated logistical challenges. Special emphasis is placed on the diversity of dimensions, weights, and stability characteristics of the transported materials. The research outlines typical forms of transport containers such as rigid plastic trays, fabric bags, standardized pallets, and specialized hanging systems. The article also provides comparative data on roll materials (including their density, weight, and packaging types) and analyzes their influence on transport equipment selection. Practical aspects of in-factory transport are covered, including the use of carts with horizontal and vertical rollers, lifting devices, and suspended rail systems. A systematized table is provided to match object categories with transport means and their specific handling requirements. The findings underscore the necessity of clear labeling, minimization of deformation risks, and ensuring appropriate environmental conditions for sensitive materials. The conclusion emphasizes that the efficiency of in- factory transport operations can be significantly improved through the unification of transportation units (containers, pallets), optimization of movement routes, and implementation of flexible automated transportation systems. The adoption of container-based transport using standardized trays and integration with automated or semi-automated handling systems (e.g., conveyors, RFID tracking) has the potential to reduce inter-operation handling time by up to 25%, improve material preservation, and reduce labor intensity. These findings are especially relevant for large-scale and mass garment production environments, where seamless logistics directly influence product cost and quality.